Efektivitas antihiperkolesterol ekstrak etanol daun salam pada tikus jantan galur wistar diabetes mellitus - Shinta Mayasari; Lindawati Setyaningrum (Jurnal Kesehatan dr. Soebandi, 2022)
Introduction: Cholesterol was one part of fat as one of the nutrients that the body needs and a high calorie producer. Plants made from natural ingredients, for example, bay leaves contain high flavonoids and are hypolipidemic as well as antioxidants that can inhibit oxidative stress. Objective: This study aims to to determine the effectiveness of the ethanol extract of bay leaves (Syzygyum polyanthum) against male white rats wistar strain diabetes mellitus with hypercholesterolemia. Methode: The experimental animals used were male wistar rats induced with streptozotocin at a dose of 30mg/kg BW. The test animals were divided into six groups, each group consisted of 5 rats. Group (I) as a normal control were given standard feed and 0.5% Na CMC, group (II) was given 0.5% Na CMC as a negative control, group (III) was given simvastatin as a positive control, groups (IV) to (VI) were given ethanol extract of bay leaves with a certain dose namely 500mg/kg BW; 750mg/kg BW, and 1g/kg BW.The data obtained were analyzed using One Way Anova statistical test with 95% confidence level. Results: The results of the analysis showed that the p value < 0.005, which means that the ethanolic extract of bay leaf has an effect on cholesterol levels in diabetes mellitus male rats strain Wistar. The effective dose that gives the optimum effect is the ethanolic extract of bay leaf 1g/kgBW. Conclusion: The ethanol extract of bay leaf 1g/kg BW was able to provide optimum antihypercholesterol effects in diabetes mellitus male rats strain Wistar